Enhanced evaporation from an oscillating liquid in a capillary tube. (April 2016) - Polezhaev, D.; Duru, P.; Plouraboué, F.
Highlights: Forced oscillation of liquid–gas interface drastically enhances evaporation in a tube. The long-time effective evaporation rate behaviour is diffusive. Effective evaporation rate can reach ten times purely diffusive evaporation. The scaling of Taylor dispersion mechanism is consistent with observations. The observed prefactor is 3 times larger than expected from Taylor dispersion. Abstract: Enhanced evaporation inside a capillary tube into which the liquid/gas meniscus oscillates is experimentally studied. It is found that the meniscus oscillation can markedly level-off the evaporation rate, while keeping an apparent diffusive behaviour. The apparent diffusive coefficient can reach a tenfold increase in the explored range of parameters. The dependence of the effect is studied by varying the capillary tube diameter, the frequency and the amplitude of the liquid oscillations. The parametric dependence of the apparent diffusive coefficient is well captured by the associated dimensionless Péclet number. A nice collapse of the experimental measurements consistent with a quadratic scaling with Péclet number is found. Such scaling is suggested by previous theoretical and experimental analysis associated with a Taylor dispersion transport mechanism. Nevertheless the prefactor of those theory is found to under-predict the observed effect by a factor three. This deviation from Taylor's dispersion driven transport predictions is discussed.